2004
DOI: 10.1002/hyp.5533
|View full text |Cite
|
Sign up to set email alerts
|

Root growth and soil water utilization of winter wheat in the North China Plain

Abstract: Abstract:Winter wheat (Triticum aestivum L.) is the major crop in the North China Plain (NCP). The monsoon climate in this region causes most rain to fall in the summer season, but during the winter-wheat growing season (October-May) the rainfall is far less than the water requirements for the crop. The efficiency of soil water use by winter wheat needs to be improved to reduce the need for irrigation. In this paper, we report the results of two seasons' work on soil water utilization, root growth and distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(111 citation statements)
references
References 26 publications
8
95
5
1
Order By: Relevance
“…Ishaq et al (2003) described that the higher RLD was obtained by deep tillage and that the RLD positively correlated with nutrient uptake and yield of grain and straw. Holloway and Dexter (1991) and Zhang et al (2004) also reported the enhancement of wheat root development into deep soil layer by deep tillage.…”
Section: Biomass Production and Yieldmentioning
confidence: 92%
“…Ishaq et al (2003) described that the higher RLD was obtained by deep tillage and that the RLD positively correlated with nutrient uptake and yield of grain and straw. Holloway and Dexter (1991) and Zhang et al (2004) also reported the enhancement of wheat root development into deep soil layer by deep tillage.…”
Section: Biomass Production and Yieldmentioning
confidence: 92%
“…In this case, the accuracy of estimated rooting depth directly influences the precision of estimates of soil moisture in the two layers. In our study, the development of crop rooting depth was estimated based on observation results in one year (Zhang, 1999). However, the real maximum rooting depth in different years might be different due to meteorological conditions and irrigation application, as discussed above.…”
Section: Strong and Weak Points Of The Current Swb Modelmentioning
confidence: 99%
“…Daily precipitation rates were measured by summing up hourly tipping-bucket measurements. The rooting depths of winter wheat and maize were reported by Zhang (1999) as a function of the number of days since planting.…”
Section: Experimental Datamentioning
confidence: 99%
“…Class A pan evaporation was measured daily. Root depths of winter wheat and maize were reported by Zhang (1999) as a function of the number of days since planting. Leaf-area index was measured by Zhang et al (2002) and Wang et al (2001).…”
Section: Field Site Descriptionmentioning
confidence: 99%